Extramammary Arm Fibroadenoma - Ahmed M. Abouzaid, MSc; Ahmed M. AbdelAzim, BSc; Karim M. Osman, BSc; Mohamed M. Soffar, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. Fibroadenoma is the most common benign mass that can affect mammary tissue in women, with an incidence of 10% of the female population worldwide being affected by such tumors. It is a painless, nontender, and highly mobile mass that can develop in different sizes and usually affects women of reproductive age (14–35 y). To the best of our knowledge, the lesion has been discovered in extramammary locations on very rare occasions. One previous report described an arm fibroadenoma, and other reports illustrated vulval fibroadenomas. This report presented a 32-year-old woman who complained of the development of a painless swelling within her upper inner right arm in the last 2 years that was investigated and then surgically excised. Histopathological examination confirmed the diagnosis of fibroadenoma.